How menu description change consumer perception about traditional gastronomy: the case of the Portuguese “Alentejo cuisine” - Guedes, David (2020)
Traditional food is an important element of cultural heritage and is gaining interest as tourism attraction. Moreover, it is based on the use of regional products, valorising seasonality and making it of interest for local economy and sustainability. Alentejo cuisine is national and internationally recognized, but different opinions are frequently reported by consumers. To promote this type of gastronomy, it is important to know how consumers perceive it and the factors that can affect such perception. An on-line survey was performed (N=516), which consisted in three main parts: 1) sociodemographic data; 2) general perception of gastronomy from Alentejo (AG); 3) evaluation of specific dishes from AG; 4) perception of the characteristics of the restaurant the participants imagined could present such menu. To test the effect of dishes description, two different on-line surveys were constructed: one presenting the list of ingredients of each dish and the other one presenting a sensorial description of the same dishes. The server where survey was performed allowed the random presentation of only one of the versions to each of the participants. It was possible to confirm that AG is seen as savoury, but at the same salty and energy dense. The menu presentation affected the way consumers expected the restaurant characteristics, giving higher rates of acceptance and trust to restaurants presenting menus with sensory description of dishes. Although AG is understood as gastronomy with a marked identity, the true is that the way dish description is presented can have an effect in the overall perception.